n‐Type Doping Effect of CVD‐Grown Multilayer MoSe2 Thin Film Transistors by Two‐Step Functionalization - Seongin Hong; Haelin Im; Young Ki Hong; Na Liu; Sunkook Kim; Jun Hong Park (Advanced Electronic Materials, 2018)
Abstract Molybdenum diselenide (MoSe2) has attracted attention as a potential semiconductor platform. However, the as‐synthesized MoSe2 field‐effect transistors (FETs) tend to exhibit the arbitrary properties of n‐type, p‐type, or ambipolar behavior due to the uncontrolled growth condition. Here, two‐step functionalization is proposed to achieve n‐doping effect and long‐term stability in chemical vapor deposition (CVD)–grown MoSe2 FETs using oxygen plasma treatment followed by the deposition of an Al2O3 layer. After the two‐step surface functionalization procedure, three types of multilayer MoSe2 FETs are all converted to n‐type with the improvement of their electrical characteristics and stability; the n‐doped multilayer MoSe2 FETs exhibit an enhancement in field‐effect mobility from 12.23 to 31.57 cm2 V−1 s−1 and a 3 times higher Ion/Ioff, compared to pristine multilayer MoSe2 FETs. This enhancement of electric performance is attributed to the oxidation of topmost MoSe2 to interfacial MoOx with SeOx induced by the oxygen plasma treatment, as well as to the existence of fixed positive charges in deposited Al2O3. The functionalized devices exhibit excellent stability against stress, as confirmed with negative bias illumination stress tests for 7200 s. Moreover, an environmental stability test for 21 days reveals no degradation in electric performance of MoSe2 FETs.